Avaliação de monitorias realizadas em um centro de ciências - Monteiro, Marco Aurélio Alvarenga [UNESP]; Monteiro, Isabel Cristina de Castro [UNESP]; Gaspar, Alberto [UNESP]; Silva, Luciene de Fátima [UNESP] (Universidade Federal de Santa Maria, 2014)
In this paper we investigate the social interaction established between monitors and student-visitors to a science museum in terms of knowledge mobilized by the explanation about principle operating of Van De Graff Generator. Our research was conducted at a university public that maintains a Center of Sciences and the data were collected through recording video and audio of the dialogues established around a demonstration experiment. Data analysis is established around the conceptual correctness of the explanations made by the monitors. We also conducted a structured interview from a single question: what is the main difficulty faced in planning and conducting his presentation at the Science Center? The results show that the monitors were not able to exceed the process description of the operation of the experimental equipment, not being able to establish an interaction that fosters discussions of scientific concepts with visitors. Our research also found that, although the university maintained a Sciences Center, not there is a link between teacher training and activities in non-formal settings.

Neste trabalho buscamos investigar a interação social estabelecida entre monitores e alunos-visitantes de um museu de ciências, do ponto de vista de conhecimentos mobilizados por aquele na explicação do gerador de Van der Graaff . Nossa pesquisa se estabeleceu numa universidade pública que mantém um Centro de Ciências e registramos, em áudio e vídeo, os diálogos estabelecidos em torno de um experimento de demonstração. A análise dos dados se estabelece em torno da correção conceitual das explicações realizadas pelos monitores. Realizamos, também, uma entrevista estruturada a partir de uma única questão: qual a principal dificuldade enfrentada para planejar e conduzir sua apresentação no Centro de Ciências? Os resultados evidenciam que os monitores, em suas falas, não ultrapassam o processo de descrição do funcionamento do equipamento experimental, não sendo capazes, portanto, de estabelecer uma interação que propicie discussões de conceitos científicos com os visitantes. Nossa pesquisa também identificou que, apesar de a Universidade manter um Centro de Ciências, não há um vínculo entre a formação do professor e as atividades realizadas em espaços não-formais.
The evaluation monitoring in a science center
Keywords: Physics teaching; Scientific literacy; Experimental demonstration activity; Ensino de física; Alfabetização científica; Atividades de demonstração experimental